Hepatic epithelioid angiomyolipoma: a report of two cases and review of the literature - Feng, Jia-Wei (Int J Clin Exp Pathol, 2018)
Hepatic epithelioid angiomyolipoma (EAML) is an uncommon mesenchymal tumor with malignant potential, which is clinically susceptible to being misdiagnosed as hepatocellular carcinoma. Therefore, accurate diagnosis of hepatic EAML and treatment is necessary. We report two cases of hepatic EAML that were identified by abdominal computed tomography (CT). The first case presented in a 37-year-old woman and was an oval-shaped liver mass, measuring 4.5×4.2×4.9 cm. The second case presented in a 51-year-old woman and was a round-shaped mass measuring 4×3.5×3.7 cm. Both patients underwent laparoscopic resection. Microscopically, we detected epithelioid and spindle-shaped cells with adipocytes. After the analysis of biomarkers, we found that both cases were positive for HMB45 and Melan-A, which helped to confirm the diagnosis. Hepatic EAML is a rare clinical tumor, which has a high rate of misdiagnosis and the final diagnosis depends on histopathologic and immunohistochemical features. Laparoscopic resection remains the recommended choice for hepatic EAML. Partial hepatic EAML has a tendency become malignant and thus long-term follow-up is needed.